2020
DOI: 10.1108/rbf-06-2020-0141
|View full text |Cite
|
Sign up to set email alerts
|

Financial literacy and financial behaviour: a bibliometric analysis

Abstract: PurposeNumerous exploratory, conceptual and empirical enquiries on financial behaviour and literacy have been conducted in the areas of economics, finance, business and management. However, no attempt was made to present a comprehensive science mapping of the area so far. Hence, the study intends to elicit the trend in the research field through synthesis of knowledge structures.Design/methodology/approachBibliometric analysis in the field of financial literacy and financial behaviour was performed on a sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
71
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(74 citation statements)
references
References 56 publications
0
71
0
3
Order By: Relevance
“…For example, Hassan (2016) had an m-index reaching 0.666. This indicated that the writer had reasonably high productivity according to the h-index and the duration of publications related to the theoretical framework (Ingale & Paluri, 2020). Fourth, shariah compliance was concentrated in Islamic financial institutions.…”
Section: Descriptive Analysis On Shariah Compliance Literaturementioning
confidence: 93%
“…For example, Hassan (2016) had an m-index reaching 0.666. This indicated that the writer had reasonably high productivity according to the h-index and the duration of publications related to the theoretical framework (Ingale & Paluri, 2020). Fourth, shariah compliance was concentrated in Islamic financial institutions.…”
Section: Descriptive Analysis On Shariah Compliance Literaturementioning
confidence: 93%
“…In two studies [60,61], the research methodology managed to map scientific knowledge based on bibliometric tools to learn the development and evolution of scientific opinions followed by authors, faculties, countries, and scientific journals; and the choices of topics, such as terms and trends in relation to the study of financial literacy.…”
Section: Literature Review and Research Assumptionsmentioning
confidence: 99%
“…The study of financial education continues to be in vogue and in this sense, it is studied in the work related to the scientometric review of the investigations that are being carried out in relation to the concept under study in this article [60,61]. In both cases, the research methodology has managed to map scientific knowledge to know the development and evolution of scientific production followed by authors, faculties, countries, scientific journals and the choice of topics, terms, and trends in relation to the study of financial literacy.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%